TINJAUAN TENTANG FAKTOR-FAKTOR PENDUKUNG TERJADINYA PROSES ASIMILASI BUDAYA MASYARAKAT BANJAR DI LINGKUNGAN MELAYU KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Firman Ridha Ridha; Zahirman '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research is based on cultural assimilation in Tembilahan district, Indragiri Hilir regency between Banjar society and Melayu society as the majority society. The formulation of this research is what is the supporting factors that influence the assimilation process of Banjar society in Melayu environment of Tembilahan district, Indragiri Hilir regency. The aim of this research is to know the supporting factors that influence the assimilation process of Banjar society in Melayu environment of Tembilahan district, Indragiri Hilir regency. The population of this research is 8657 and the sample is 70 with sampling is the process selecting. The data instrument is 25 questionnaire and 6 interview question. The data is analyzed with qualitative descriptive analysis. From the analysis, writer got 51.43% as the dominant answer for chances to be balance in economy aspects, 59.72% for respect the other cultures, 53.21% for the fair attitude from the authorities in society, 55.71% for the similarities of cultural element, and 54.29% for the same enemies from other aspect. Based on Suharsimi Arikunto, dominant is set between 50.01% - 70.00%, so the hypothesis “The Tolerance and Amalgamation Factors toward the Assimilation Process of Banjar Society in Melayu Environment of Tembilahan District, Indragiri Hilir Regency” is rejected or ignored. Keywords: The Factors Supporting Occurrence Assimilation Process